Dissection of the FCGR3A association with RA: increased association in men and with autoantibody positive disease. Issue 6 (20th August 2009) - Robinson, James I; Barrett, Jennifer H; Taylor, John C; ,; Naven, Marc; Corscadden, Diane; ,; Barton, Anne; Wilson, Anthony G; Emery, Paul; Isaacs, John D; Morgan, Ann W
Abstract : Objectives: Genome-wide association studies in rheumatoid arthritis (RA) have failed to examine the FCGR gene cluster because of the confounding effects of segmental duplication. This study aimed to replicate previous candidate gene studies that had identified a significant association between the FCGR3A -158V allele and RA and then sought to estimate specific subgroup effects. Methods: FCGR3A -158F/V genotyping was undertaken in a UK Caucasian replication cohort comprising 2049 patients with RA and 1156 controls. Subgroup analyses assessing the magnitude of association according to gender and autoantibody (rheumatoid factor (RF) and cyclic citrullinated peptide (CCP)) status were undertaken in a pooled cohort of 2963 patients with RA and 1731 controls. Logistic regression was used to test for interaction between FCGR3A and HLA-DRB1 shared epitope (SE) alleles. Results: In the combined RA cohort, borderline association with homozygosity was found for the FCGR3A -158V allele (OR 1.2, p=0.05), which was stronger in men (OR 1.7, p=0.01). Stratification by autoantibody status showed an increased risk in RF and CCP positive RA. Analysis of the FCGR3A-158V and HLA-DRB1 SE interaction revealed roles for both genes in susceptibility to autoantibody positive RA, with no evidence of interaction. Conclusions: FCGR3A is a risk factor for the development of autoantibody positive RA, particularly in men, with evidence of a multiplicative effect with HLA-DRB1 SE.